La Contabilidad Gerencial y su impacto en la toma de decisiones en la fábrica industrial INDUACCS de la parroquia Unamuncho, cantón Ambato, provincia de Tungurahua durante el primer semestre del año 2022. - Chango Chato, Evelyn de los Ángeles (2024)
This integrative project was developed in the “INDUACCS” industrial factory, dedicated to the seats and accessories production for bodywork, cabinets, specific sizes beds, moreover to offer welding services. The problem focuses on the theoretical and practical ignorance from management accounting and its tools and inadequate decision making. The main aim, it is to analyze the management accounting impact on decision making, by using the cost-volume-profit model as an administrative tool. For the methodology, it was applied a quantitative approach descriptive, field and documentary research based on the different safe research and reliable bibliographic sources. The cost-volume-utility model developed in Excel allowed to determine fixed, variable and production costs and identify the break-even point, contribution margin and the changes assessment in the variables. Starting at the different calculations, scenario analysis and got results, they could be established the following decisions: It is profitable, which the seats production to increase, since it will allow the enterprise to give a higher production level and a 31% from utility, before taxes. In the beds case, it will be essential to reduce variable costs by 10%, because, it results in a significant increase in the operational utility and an operational margin 31%. The scenario, which favors cabinets is also the variable costs reduction and it presents an operational margin 31%, this indicates, what the variable costs reduction can be an effective strategy for improving the profitability from factory without compromising production or income. In conclusion, it must be taken into account that knowing and understanding management accounting, its functions and applications and especially the designed model execution will make possible a correct decision-making and economic, administrative and productive growth and development from INDUACCS enterprise.